Predictors of antidepressant use in the English population: analysis of the Adult Psychiatric Morbidity Survey. (24th March 2020) - Boyle, S.; Murphy, J.; Rosato, M.; Boduszek, D.; Shevlin, M.
Abstract : Objectives: The rate of antidepressant use in the United Kingdom has outpaced diagnostic increases in the prevalence of depression. Research has suggested that personal and socioeconomic risk factors may be contributing to antidepressant use. To date, few studies have addressed these possible contributions. Thus, this study aimed to assess the relative strength of personal, socioeconomic and trauma-related risk factors in predicting antidepressant use. Methods: Data were derived from the Adult Psychiatric Morbidity Survey ( n =7403), a nationally representative household sample of adults residing in England in 2007. A multivariate binary logistic regression model was developed to assess the associations between personal, socioeconomic and trauma-related risk factors and current antidepressant use. Results: The strongest predictor of current antidepressant use was meeting the criteria for an ICD-10 depressive episode [odds ratio (OR)=9.04]. Other significant predictors of antidepressant use in this analysis included English as first language (OR=3.45), female gender (OR=1.98), unemployment (OR=1.82) and childhood sexual abuse (OR=1.53). Conclusions: Several personal, socioeconomic and trauma-related factors significantly contributed to antidepressant use in the multivariate model specified. These findings aid our understanding of the broader context of antidepressant use in the United Kingdom.